The inexpensive noise control method -a case study - Ramakrishnan, Ramani (Canadian Acoustics, 2004)
An audit noise measurement program to control the effluent from four ovens of a industrial facility was presented. The four of the exhaust stacks form the facility were connected to a pollution control system and the output from the pollution control system was exhausted through a single stack. The measurement indicated that the exhaust stack of the pollution control system generates the offending tonal noise. The residential noise levels showed the plant was within 1-2 dB of the guideline limits.